Peran Brand Image, Trust, dan Equity dalam Membangun Loyalitas Pelanggan Kosmetik - Mandasari, Rosita Trisna; Jatmiko, Udik; Zamzam, Nurali Agus Najibul (Commodities, Journal of Economic and Business, 2025)
This study examines the influence of brand image, brand trust, and brand equity on customer loyalty for Wardah halal cosmetics at Counter Nikisae Tulungagung, Indonesia. Against the backdrop of rapid growth in the global halal cosmetics market, the research addresses gaps in understanding how these brand elements interact in offline retail settings. Using quantitative methods with accidental sampling (n=99), data was collected through validated questionnaires and analyzed via multiple linear regression. Results reveal all three variables significantly affect loyalty (p<0.01), with brand equity showing the strongest impact (?=0.343), followed by brand image (?=0.316) and brand trust (?=0.311). The model explains 35.1% of loyalty variance (R²=0.351), highlighting the particular importance of religious values in brand equity formation and the role of in-store experiences in building trust. These findings enrich the Customer-Based Brand Equity theory in halal contexts while providing practical insights for omnichannel strategy development in Indonesia's growing Islamic cosmetics sector.